ANALISIS CRITICAL THINKING SKILLS SISWA KELAS IX TEKNIK PEMESINAN SMKN 1 GOMBONG PADA PEMBELAJARAN TEKNIK BUBUT BERDASARKAN WATSON-GLASER CRITICAL THINKING APPRAISAL - Damar Prihantoro; Taufik Wisnu Saputra (Nozel : Jurnal Pendididikan Teknik Mesin, 2025)
Critical Thinking Skills (CTS) is a fundamental ability that every student must have. In the modern era of 21st century learning, students are required to have broad understanding, creativity, the ability to solve problems, a nd ways of thinking from various points of view. This research is research on critical thinking skills in Vocational High School students. The instrument used is The Watson-Glaser Critical Thinking Appraisal (WGCTA) where the focus of measurement includes 5 indicators, namely argumentation ability, assumption ability, deduction ability, interpretation ability and conclusion drawing ability. This research uses quantitative methods because the data used are the results of pure test scores. This research was conducted on class 11 students of the Machining Engineering study program at State Vocational Hight School 1 Gombong. Critical thinking skills (CTS) measurement focuses on learning lathe machining techniques. The research results showed that 52.77% of students had very high critical thinking skills (CTS) abilities or classification A. Meanwhile, 2.78% of students had low abilities or classification D. Students' highest abilities are dominated by indicators of drawing conclusions. Meanwhile, the highest average score for classification A is 87.37 and the lowest for classification D is 62. Overall the critical thinking skills of the 5 WGCTA indicators in class 11 students of the machining engineering study program at State Vocational Hight School 1 Gombong have classification A.